Fusobacterium necrophorum Pharyngitis Complicated by Lemierre's Syndrome. (6th December 2016) - Faraone, Antonio; Fortini, Alberto; Nenci, Gabriele; Boccadori, Costanza; Mangani, Valerio; Oggioni, Roberto
Abstract : We report the case of an 18-year-old woman who was referred to our outpatient clinic because of a 2-week history of sore throat, high fever, and neck tenderness unresponsive to a 7-day amoxicillin/clavulanic acid course. Infectious mononucleosis was initially suspected, but an extremely high value of procalcitonin and clinical deterioration suggested a bacterial sepsis, prompting the patient admission to our internal medicine ward. Blood cultures were positive for Fusobacterium necrophorum . CT scan detected a parapharyngeal abscess, a right internal jugular vein thrombosis, and multiple bilateral lung abscesses, suggesting the diagnosis of Lemierre's syndrome. The patient was treated with a 2-week course of metronidazole and meropenem with a gradual clinical recovery. She was thereafter discharged home with metronidazole and amoxicillin/clavulanic acid for 14 days and a 3-month course of enoxaparin, experiencing an uneventful recovery. The present case highlights the importance of taking into consideration the Lemierre's syndrome whenever a pharyngotonsillitis has a severe and unusual course.